Rancang Bangun Sistem Monitoring Kualitas Air di Pabrik Air Mineral P2s2 CV. Hafas Situbondo Berbasis Internet of Things (IoT) - Noer Khalis; Abd. Ghofur; Farihin Lazim (Universitas Islam Raden Rahmat, Malang, 2024)
The rapid development of technology, especially internet network technology, has brought progress in various aspects of life. One of the latest innovations is the Internet of Things, where objects in the real world can communicate with each other via the internet network. Water is a vital element in life, but its quality is often threatened by pollution, so monitoring water quality is crucial. The mineral water industry has an important role in providing clean and safe water, with water quality affecting consumer health. This research aims to design an IoT-based water quality monitoring system at the P2S2 CV mineral water factory. Hafas Situbondo. This system uses the pH4502c and ESP8266 sensors to monitor water quality in real-time, and send data to Firebase for further analysis. Testing shows that the system is capable of providing timely and accurate information, improving monitoring efficiency and response to potential contamination. Thus, it is hoped that this system can increase product safety and consumer confidence in the mineral water produced.